MECHANISMS OF DEVELOPING CREATIVE THINKING OF STUDENTS THROUGH DIGITAL TECHNOLOGIES - Khamraeva Nazira Ravshanovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article talks about the necessity of the Internet and computers for all of us today, about the fact that the lessons are interesting and effective with the help of technology, about the fact that the thinking circle of young students is growing, about the fact that their thinking is gaining a worldview.